DEVELOPMENT OF UNLIMITED AVIATION IN THE WORLD AND UKRAINE:ANALYSIS OF FEATURES AND TECHNICAL CHARACTERISTICS - Бабій, Ю.О.; Поліщук, В.В.; Мацишин, М.О.; Мартинюк, В.П.; Мартинюк, О.В.; Черноусов, Д.О. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2022)
The capabilities of unmanned aerial vehicles are constantly growing, the scope of their use is expanding, combat survivability is increasing. Most of them are small, low optical and radar contrast, so they are less vulnerable to enemy air defenses. At the same time, in the armed forces of the world's leading countries, in particular the Armed Forces of Ukraine, unmanned aerial vehicles are increasingly used instead of manned aircraft to perform combat tasks of reconnaissance, battlefield surveillance, destruction of ground targets, creation of false air targets and more. In general, the assessment of modern armed conflicts shows an increase in the intensity of mass use of unmanned aerial vehicles to solve combat tasks at various levels (tactical, operational and strategic), which significantly changes the course of armed struggle in the air. Unmanned aerial vehicles have been and remain one of the main means, which determines not only the enthusiasm of the initiative, but also the result of the confrontation in general.Analysis of publications allows us to understand the use of unmanned aerial vehicles, the effectiveness of unmanned aerial vehicles in solving various problems, as well as their advantages and disadvantages, but does not reveal ways and experience of using unmanned aerial vehicles in today's military conflict. This article reveals the trends in the combat use of unmanned aerial vehicles, analyzes the use of unmanned aerial vehicles based on the experience of their combat use in combat conflict with the Russian Federation, which, in particular, showed that the struggle of air defense forces and forces in the armed conflict Aviation is ineffective due to a number of factors, in particular due to the advanced development of these air attack means in relation to existing air defense firepower. In addition, the paper identifies the importance of unmanned aerial vehicles on the peculiarities of warfare, its further nature of action and trends in the further application and features of modern martial arts with the leading role of aviation. Thus, the air operation (both for defense and offensive purposes) is an important component of the operation to repel armed aggression and aggravate the military-political conflict and full-scale armed conflict of the Russian Federation requires a more detailed analysis of combat applications of modern unmanned aerial vehicles.

Можливості безпілотних літальних апаратів постійно зростають, сфера їхнього використання розширюється, бойова живучість підвищується. Більша кількість з них має малі розміри, низьку оптичну та радіолокаційну контрастність, тому вони менш уразливі засобами протиповітряної оборони противника. Разом з тим, у збройних силах провідних країн світу, зокрема Збройними Силами України, безпілотні літальні апараті все частіше використовуються замість пілотуємих літальних апаратів для виконання бойових завдань з ведення розвідки,спостереження за полем бою, знищення наземних цілей, створення хибних повітряних цілей тощо. Загалом оцінка збройних конфліктів сучасності свідчить про збільшення інтенсивності масованого застосування безпілотних авіаційних комплексів для вирішення бойових завдань різних рівнів (тактичного, оперативного та стратегічного), що суттєво змінює перебіг збройної боротьби у повітрі. Безпілотна авіація була і залишається одним із основних засобів, що зумовлює не тільки захоплення ініціативи, але і результат протиборства взагалі. Аналіз публікацій дозволяє зрозуміти порядок застосування безпілотної авіації, ефективність безпілотних літальних апаратів в ході вирішення різних завдань, а також їх переваги та недоліки, однак не розкрито способи та досвід застосування безпілотних літальних апаратів у сьогоднішньому воєнному конфлікті. У даній статті розкрито тенденції бойового застосування безпілотної авіації, здійснено аналіз застосування безпілотної авіації на основі досвіду їх бойового застосування під час ведення збройного конфлікту з російською федерацією, який, зокрема, показав, що боротьба сил та засобів протиповітряної оборони в збройному конфлікті російської федерації проти безпілотної авіації єнедостатньо ефективною внаслідок ряду факторів, зокрема через випереджальний розвиток даних засобів повітряного нападу по відношенню до існуючих вогневих засобів протиповітряної оборони. Крім того, у роботі визначено значення безпілотної авіації на особливості ведення війни, її подальший характер дії та тенденції розвитку подальшого застосування та особливості сучасного військового мистецтва при провідній ролі авіації. Таким чином, повітряна операція (як з оборонними, так і з наступальними цілями) є важливим компонентом операції з відсічі збройної агресії і загострення воєнно-політичного конфлікту. Тому повномасштабний збройний конфлікт російської федерації вимагає більш детального аналізу особливостей бойового застосування сучасної безпілотної авіації України.
РОЗВИТОК БЕЗПІЛОТНОЇ АВІАЦІЇ У СВІТІ ТА УКРАЇНІ: АНАЛІЗ ОСОБЛИВОСТЕЙ ТА ТЕХНІЧНИХ ХАРАКТЕРИСТИК
Keywords: martial law; unmanned aerial vehicles; unmanned strike aircraft; intelligence; drone; air defense; воєнний стан; безпілотна авіація; безпілотна ударна авіація; розвідка; дрон; протиповітряна оборона